The China shock and the geographic dispersion of innovation in Brazil - Scatimburgo, Pedro Roveri (2024)
This study analyzes how international trade shocks, specifically the China Shock, impacted the geographic and sectoral distribution of innovation in Brazil. Utilizing data on Brazilian patent applications, I employ a shift-share IV method to assess the effects of import supply and export demand shocks on patent applications across the country’s microregions. The results show a positive correlation between the export demand shock and patent applications in the Chemistry sector, closely tied to the agriculture and extraction industries, and a negative correlation in regions and sectors traditionally focused on manufacturing, notably in Mechanical Engineering and Civil Engineering. This shift indicates a realignment of innovation, from a focus on manufacturing to agriculture and extraction, reflecting changes in comparative advantages shaped by the dynamics of global trade. The study contributes to the understanding of the complex interaction between international trade shocks and the distribution of innovation, highlighting the dual impact of China’s rise on the Brazilian innovation landscape. This analysis suggests that while the export demand shock stimulated innovation in certain sectors, it simultaneously led to a contraction in regions traditionally strong in manufacturing, underscoring the broader implications of global economic displacements on national innovation systems.